2016
DOI: 10.1017/jfm.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

On the reduction of aerofoil–turbulence interaction noise associated with wavy leading edges

Abstract: An aerofoil leading-edge profile based on wavy (sinusoidal) protuberances/tubercles is investigated to understand the mechanisms by which they are able to reduce the noise produced through the interaction with turbulent mean flow. Numerical simulations are performed for non-lifting flat-plate aerofoils with straight and wavy leading edges (denoted by SLE and WLE, respectively) subjected to impinging turbulence that is synthetically generated in the upstream zone (freestream Mach number of 0.24). Full threedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
144
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 38 publications
9
144
0
Order By: Relevance
“…It has been demonstrated by the authors of the current paper Haeri et al 2014;Narayanan et al 2015;Chaitanya et al 2015b;Kim et al 2016) and others that introducing leading edge serrations can be an effective method of reducing far field noise. This previous work was limited in scope and provided no insight in the optimum serration geometry.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has been demonstrated by the authors of the current paper Haeri et al 2014;Narayanan et al 2015;Chaitanya et al 2015b;Kim et al 2016) and others that introducing leading edge serrations can be an effective method of reducing far field noise. This previous work was limited in scope and provided no insight in the optimum serration geometry.…”
Section: Introductionmentioning
confidence: 76%
“…Through numerical simulations based on the compressible three-dimensional Euler equations and a synthetic eddy method for the turbulence generation, Kim et al (2016) investigated the noise reduction mechanisms of sinusoidal leading edge serrated aerofoils. They found that the surface pressure fluctuations along the leading edge exhibit a source cut-off effect due to oblique edge which results in reduced radiated sound power levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second objective of this paper, therefore, is to exploit this unique morphology of the owl wing for the leading edge serration on an aerofoil. As pointed out by Kim et al 6 , the remaining contributor to the interaction noise radiation for a serrated leading edge is related to the flow dynamics at the sawtooth trough region. Because each consecutive sawtooth tips of a curved leading edge serration exhibits a spanwise offset to the sawtooth trough at the downstream, the incoming turbulence structures could be shielded by the sawtooth tip.…”
Section: Introductionmentioning
confidence: 89%
“…They suggested that the level of broadband noise reduction is a strong function of the serration amplitude h, and is less sensitive to the serration wavelength . An inviscid numerical study by Kim et al 6 exhibited a de-correlation of the surface pressure fluctuation and the far field noise on a serrated leading edge. In particular, the noise source at the mid-region of the oblique edge becomes ineffective across the mid to high frequency range.…”
Section: Introductionmentioning
confidence: 99%